2006
DOI: 10.1037/0735-7044.120.6.1389
|View full text |Cite
|
Sign up to set email alerts
|

Sexual experience increases nitric oxide synthase in the medial preoptic area of male rats.

Abstract: Nitric oxide in the medial preoptic area (MPOA) is important for the expression and sensitization of male sexual behavior. In this article, the authors report that repeated sexual experience (mating for 2 hr on each of 3 days) increased levels of nitric oxide synthase (NOS) in the MPOA of male rats, regardless of whether they mated on the day they were given an overdose of sodium phenobarbital. This effect resulted from the previous experience and not acute mating, as NOS was not increased 2 hr after the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
0
25
1
Order By: Relevance
“…The preoptic area of gars houses a remarkable population of nitrergic cells distinct from the TH-ir, ChAT-ir, and CB-ir populations also observed in this region. The presence of nitrergic cells in the preoptic area is a highly conserved feature observed in all anamniotes studied (Table 2), whereas it is a more variable feature in amniotes, being present in birds [Brüning, 1993;Cozzi et al, 1997;Atoji et al, 2001] and some species of reptiles and mammals [Hadeishi and Wood, 1996;Domínguez et al, 2006;Nutsch et al, 2014], where the role of NO in sexual behavior has been demonstrated [Nutsch et al, 2014]. It should be noted that gene expression data have highlighted that the preoptic area does not belong to the hypothalamus but it is part of the subpallial telencephalic territory [see Moreno and González, 2011;Domínguez et al, 2015] that is topologically adjacent to the dorsal hypothalamic territory, and similar observations have been obtained for gars [González et al, 2014].…”
Section: Forebrainmentioning
confidence: 99%
“…The preoptic area of gars houses a remarkable population of nitrergic cells distinct from the TH-ir, ChAT-ir, and CB-ir populations also observed in this region. The presence of nitrergic cells in the preoptic area is a highly conserved feature observed in all anamniotes studied (Table 2), whereas it is a more variable feature in amniotes, being present in birds [Brüning, 1993;Cozzi et al, 1997;Atoji et al, 2001] and some species of reptiles and mammals [Hadeishi and Wood, 1996;Domínguez et al, 2006;Nutsch et al, 2014], where the role of NO in sexual behavior has been demonstrated [Nutsch et al, 2014]. It should be noted that gene expression data have highlighted that the preoptic area does not belong to the hypothalamus but it is part of the subpallial telencephalic territory [see Moreno and González, 2011;Domínguez et al, 2015] that is topologically adjacent to the dorsal hypothalamic territory, and similar observations have been obtained for gars [González et al, 2014].…”
Section: Forebrainmentioning
confidence: 99%
“…Increased sensitivity to testosterone via MPOA AR might play a role in nitric oxide synthase-mediated local dopamine release. Indeed, levels of nitric oxide synthase in the MPOA have been shown to be elevated in sexually experienced male rats (Dominguez et al, 2006), indicating that this circuit is also sensitive to sexual experience and potentially pointing to an interaction between gonadal steroids and dopamine within the MPOA. Elucidating these interactions would provide insight into the mechanisms of plasticity in the male brain that are recruited during reproductive experience.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual experience increases nNOS activity in the MPOA in male rats (Dominguez et al 2006). Our previous study showed that sexually experienced rats treated with EGb 761 exhibited a significant increase in intromission and ejaculation frequency, but EGb 761 did not influence nNOS-IR cells in the MPOA (Yeh et al 2011b), suggesting that enhanced male copulatory performance in sexually experienced rats treated with EGb 761 may not be related to central nNOS activity in the MPOA.…”
Section: L6 S1mentioning
confidence: 97%